Criminal law categories as ideological constructs: the case of human trafficking - Fouladvand, Shahrzad (Demystifying power, crime and social harm, 2023)
Box’s argument that ‘criminal law categories are ideological constructs’ (Box, Power, crime and mystification, Tavistock, London, 1983, 7) opens up an important space for dialogue between criminology and critical studies of criminal law. In this chapter we apply Box’s insight to a type of criminalization that is much more prominent today than it was when Power, Crime and Mystification was published: transnational criminal law. We focus particularly on human trafficking and modern slavery. Transnational criminal law is based on international agreements which require states to criminalise certain behaviour, including for example corruption, money laundering and human trafficking. As Box’s analysis would predict, it tends to reflect coalitions of interests which may not directly reflect the interests of a single class or state. In many instances, including human trafficking, the harms it targets are real, serious and widespread. Nevertheless, Box’s analysis also predicts that transnational criminal law will be interpreted in ways that create ideologically useful images of typical offenders, while allowing elites to engage in the very activities it criminalises, and diverting attention from analogous forms of harm and exploitation which remain perfectly legal. Building on Box’s work, this chapter considers the ways in which laws on human trafficking and modern slavery contribute to demonising illegal immigration, sex work and black ‘gangsters’, while legitimising other forms of labour exploitation. It also highlights the extent of corporate and state crime in relation to human trafficking. We suggest that from a social harm perspective it.